Transgender Learners’ Perspectives on their Well-being and Wellness after Vocational Training in South Punjab - Gouhar Pirzada; Aroosa Liaqat; Dr Sajid Masood (Dialogue Social Science Review (DSSR), 2025)
This study investigates the perspectives of transgender learners in South Punjab on their well-being after completing vocational training. To study the key domains of well-being, 100 transgender people were asked to complete open-ended surveys addressing mental, social, physical, community, financial, and work issues. The results highlight the difficulties and support for well-being within this group, focusing on events after their training. By studying how transgender individuals manage, connect, handle their finances, and remain motivated at work, this study hopes to suggest ways to boost the quality of life of transgender people. The study helps explain how vocational training affects a person's overall well-being, providing ideas for action for leaders, teachers, and community supporters.